Influence of pre-harvest sprays of calcium chloride on fruit storage quality and softening of ‘fengtangli’ (Prunus salicina L.) plum - Yunxing Wu; Xiaoqing Dong; Yongchao Zhu; Hong Chen (CyTA - Journal of Food)
The aim of the experiment was to investigate the effect of pre-harvest calcium chloride (CaCl2) sprays on post-harvest quality and cell wall metabolism of the “Fengtangli” plum fruit. The results showed that calcium treatment could effectively delay the rise of pectin methylesterase (PME), polygalacturonase (PG), β-galactosidase (β-Gal), and cellulase (Cx) activities, which in turn could effectively inhibit the accumulation of protopectin (PP), reduced water-soluble pectin (WSP), ion-bound pectin (ISP), and covalently bound pectin (CSP). Furthermore, calcium treatment significantly down-regulated the expression of the Psβ-Gal, PsPME, and PsPG genes in “Fengtangli” plums at the early stage of low-temperature storage and the expression of the PsCx gene at the middle and late stages of storage. These findings showed that the pre-harvest spraying of calcium can effectively delay the softening of plums by regulating cell wall metabolism and maintaining fruit quality.